2005
DOI: 10.1002/chem.200500443
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Total Synthesis of Fredericamycin A: An Intramolecular Cycloaddition Pathway

Abstract: The asymmetric total synthesis of the potent antitumor antibiotic fredericamycin A ((S)-1) was achieved by the intramolecular [4+2] cycloaddition of the silylene-protected styrene derivative (S)-7 followed by the aromatic Pummerer-type reaction of the sulfoxide (S)-5. Although we had already succeeded in the total synthesis of racemic 1 by the same approach, synthesis of its asymmetric version was more complicated than we had expected due to the difficulties involved in constructing the quaternary carbon cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 79 publications
(24 reference statements)
0
12
0
Order By: Relevance
“… Specifically, Indinavir, one of World Health Organization’s List of Essential Medicines, is used for treating HIV/AIDS. Fredericamycin A displays potent antitumor activity against a variety of in vivo tumor models, involving P388 leukemia, B16 melanoma, and CD8F mammary. SB 209670 exhibits a highly potent antagonist selective for the endothelin receptors.…”
mentioning
confidence: 99%
“… Specifically, Indinavir, one of World Health Organization’s List of Essential Medicines, is used for treating HIV/AIDS. Fredericamycin A displays potent antitumor activity against a variety of in vivo tumor models, involving P388 leukemia, B16 melanoma, and CD8F mammary. SB 209670 exhibits a highly potent antagonist selective for the endothelin receptors.…”
mentioning
confidence: 99%
“…The second approach was accomplished by a lipase-catalyzed desymmetrization and kinetic resolution followed by the aromatic Pummerer-type reaction. In the total synthesis of racemic fredericamycin A, we demonstrated that only the aromatic Pummerer-type reaction could introduce the oxygen atom at the B-ring . Moreover, we reported the stereoselective synthesis of the ABCDE-ring by using the EVE-mediated desymmetrization .…”
Section: Development Of New Reactions and Applicationsmentioning
confidence: 99%
“…7 Derivatives 3 belonging to the same type of 2,2-disubstituted 1,3-indandiones are the focus of considerable synthetic efforts: over 30 research papers describing more than 400 new compounds of type 3 have been published only during the past five years. 8 The interest toward derivatives 3 is motivated by the presence of the spiro-1,3-indandione moieties in various biologically active compounds, both natural 9 and synthetic. 10 Currently, development of new catalytic approaches allows the preparation of these derivatives stereo-and enantio-selectively from available precursors in 1 -2 synthetic steps.…”
Section: Introductionmentioning
confidence: 99%